Effectiveness of a forgiveness-based intervention to promote post-traumatic growth in hemodialysis patients: an experimental controlled study - Xie, Qin; Zhang, Yue; Ye, Yansheng; Wang, Hong; Luo, Dan; Mu, Changwei (Frontiers in Psychology, 2025)
BackgroundPost-Traumatic Growth (PTG) is a key indicator of psychological wellbeing and quality of life in patients undergoing Maintenance Hemodialysis (MHD). Forgiveness, as a positive psychological process, involves transforming negative responses into adaptive ones after trauma and may facilitate PTG by reducing resentment and promoting emotional recovery. However, empirical evidence on the effectiveness of forgiveness-based interventions in enhancing PTG remains limited, particularly among hemodialysis patients.ObjectiveThis study aimed to develop a forgiveness-based intervention program for post-traumatic growth in patients undergoing MHD and to evaluate its effectiveness.MethodsThis study was conducted in a tertiary hospital in Yunnan Province with 78 maintenance hemodialysis patients assigned to an intervention group (n = 39) and a control group (n = 39). The intervention group received an 8 week nurse-delivered forgiveness-based psychological program alongside routine care, while the control group received routine care only. Post-traumatic growth, forgiveness, coping style, anxiety, depression, heart rate, and blood pressure were assessed at baseline, post-intervention, and 3 month follow-up. Data analysis was performed using descriptive statistics, independent t tests, chi-square or Fisher's exact tests, repeated-measures ANOVA, and paired t tests. Statistical significance was set at p < 0.05.ResultsBoth groups were comparable at baseline across all outcome measures. Post-traumatic growth significantly increased in the intervention group compared to the control group at the end of the intervention (T2: p < 0.001) and at three-month follow-up (T3: p < 0.001). Forgiveness scores were also significantly higher in the intervention group at both T2 and T3 (p < 0.001). Positive coping showed significant improvement at both time points (p < 0.001), while negative coping, anxiety, and depression scores were significantly reduced (all p < 0.01). No significant differences were found between groups in heart rate or blood pressure at any time point.ConclusionsThe forgiveness-based intervention program showed beneficial effects on post-traumatic growth, forgiveness, and emotional adjustment in patients receiving maintenance hemodialysis. As a low-cost approach, it has the potential to be incorporated into routine dialysis care to help promote post-traumatic growth in patients receiving maintenance hemodialysis.Clinical trial registrationhttps://www.chictr.org.cn/showproj.aspx?proj=184556, identifier Chinese Clinical Trial Registry (ChiCTR2200066914).